PEDAGOGICAL FOUNDATIONS OF SYSTEMATIC ANALYSIS IN IMPROVING THE EDUCATIONAL PROCESS - Akhrorova Umida Khamidullayevna (Web of Journals Publishing, 2025)
This article provides insights into the pedagogical foundations of systematic analysis in improving the educational process, and comprehensively covers the role and importance of systematic analysis in implementing the requirements of the state for the development of the education system today and in further developing the education system.
Keywords: Pedagogical activity, the concept of the pedagogical system, the pedagogical team, educational work, pedagogical systems, small systems, medium pedagogical system, large systems, the educational process.